Comparative effectiveness of statins for chronic obstructive pulmonary disease patients with pulmonary hypertension: systematic review and network meta-analysis - Xu, Guobo; Zhang, Rui; Huang, Wenrui; Du, Xuelian; Xu, Weifang (Frontiers in Medicine, 2025)
Introduction and objectivesStatins may effectively treat PH-COPD, but current guidelines do not endorse their use. This study aims to assess the comparative effectiveness and safety of Statins in adult patients with pulmonary hypertension associated with chronic obstructive pulmonary disease (PH-COPD) through a systematic review and network meta-analysis.Materials and methodsWe searched 8 databases for randomized controlled trials (RCTs) involving Statins in individuals with PH-COPD from inception to July 1, 2024. We assessed bias using the ROB 2.0 tool and evaluated evidence quality with the CINeMA framework. We employed a Bayesian network meta-analysis approach to assess outcomes including pulmonary artery pressure, exercise tolerance, lung function, oxygenation parameters, inflammatory markers, and vasoactive substances. Using RStudio and other software, we generated forest plots, league tables, and SUCRA curves to evaluate both direct and indirect comparisons.ResultsWe analyzed data from 41 RCTs involving 3,606 participants. Our analysis revealed that all 5 statins were effective in reducing Systolic Pulmonary Artery Pressure (sPAP) compared to standard treatment (ST). Rosuvastatin was the most effective, significantly lowering sPAP [MD = –8.8; (95%CI –11.68, −5.85)] and IL-6 (MD = -16.41; 95%Cl − 29.64, −3.04) and improving the 6-Minute Walk Distance (6MWD) (MD = 67.03; 95%Cl 2.77, 130.86). Atorvastatin 20 mg was the most effective in improving lung function, increasing PO2, reducing inflammatory markers such as TNF-α and hs-CRP, and lowering ET-1. Finally, Simvastatin 20 mg + ST was identified as the most effective regimen for reducing PCO2 and increasing NO levels.ConclusionOur study demonstrates that statins are more effective than standard treatment for adults with PH-COPD. Rosuvastatin is the most effective at reducing sPAP. It also improves the 6MWD and lowers IL-6 levels. Additionally, statins have significantly enhanced lung function, oxygenation parameters, and inflammatory markers in PH-COPD patients, with Atorvastatin showing the best performance in these areas.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024573849, identifier CRD42024573849.